Achievement of business capital assistance for asnaf entrepreneurs studying at zakat institutions in Malaysia - Abang Abai, Dayang Shobihah; Awang, Mohd Daud; Hamli, Hadi (Human Resource Management Academic Research Society, 2022)
The goal of supplying capital is to generate long-term revenue and assist asnaf in transitioning from zakat receivers to zakat payers. In this context, it is frequently asserted that the aid channelled is ineffective from an economic standpoint. This is because most aid recipients fail, mainly due to a lack of business capital. As a result, this research aims to determine the extent to which zakat business capital aid is distributed in Malaysian zakat institutions. This study employs a qualitative research approach through interview techniques and document review. Semi-structured interviews and document evaluation were used to obtain data for this study. The researcher manually managed and analysed the study data using the thematic method. The study results reveal that the research successfully answered all of the researchers' questions. The topic of the researcher's queries was capital support, specifically financial and equipment assistance. Researchers expect that the study's findings will be valuable to zakat institutions in improving the effectiveness of zakat distribution to the poor in this country.